Menanamkan Moderasi Beragama Sejak Dini: Integrasi dalam Pembelajaran SKI di Kelas Tinggi Madrasah Ibtidaiyah (MI) - Robbani Hamdan Hamdan (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study aims to examine the integration of values of religious moderation through the teaching of Islamic Cultural History (SKI) in upper-grade classes of Madrasah Ibtidaiyah (MI). The background of this research is based on the importance of strengthening students’ moderate character amidst the rising phenomena of intolerance and radicalism, as well as the suboptimal implementation of moderation values in SKI instruction, which still tends to be cognitively oriented. This study employs a qualitative approach with a case study design. The research subjects included SKI teachers, students in grades IV–VI, and the madrasah principal, selected through purposive sampling. Data collection techniques included participant observation, in-depth interviews, and document analysis, followed by analysis using the interactive model by Miles, Huberman, and Saldana, comprising the stages of data reduction, data presentation, and drawing conclusions. Research findings indicate that the integration of religious moderation values into Islamic Studies (SKI) instruction is carried out through three main aspects: content, methods, and assessment. Values such as tolerance (tasamuh), balance (tawazun), justice (i‘tidal), and moderation (tawasuth) are integrated into history content, particularly through the exemplary stories of Islamic figures. Participatory and contextual teaching methods, such as storytelling, discussion, and problem-based learning, have proven effective in internalizing these values. However, implementation still faces challenges in the form of limited teacher competencies, the dominance of conventional methods, and evaluations that do not yet address affective aspects. The integration of religious moderation values into Islamic Cultural History (SKI) learning positively contributes to the formation of students’ tolerant and inclusive character. Therefore, strengthening teachers’ competencies, fostering learning innovations, and developing authentic assessments are necessary to optimize the internalization of religious moderation values in elementary madrasahs (MI).